ANALISIS KEMAMPUAN LITERASI SAINS DAN METAKOGNTIF PESERTA DIDIK - Sukowati, Dwi; Rusilowati, Ani; Sugianto, Sugianto (Universitas Negeri Semarang, 2017)
Government demands on the learning process always put their science lessons. The most important thing in learning science is the scientific literacy skills and high-level thinking skills are metacognitive. The purpose of this study is to describe and analyze the relationship between metacognitive abilities scientific literacy with students in some secondary schools are implementing Curriculum 2013. The method used is a sequential explanatory mixed method. Quantitative data analysis techniques using parametric statistical and qualitative data analysis using grounded theory. The results showed the average value of scientific literacy skills every school is less than 50, included in the poor category. In terms of distribution of score points ability of scientific literacy acquired under the target distribution points Organisation for Economic Co-operation and Development (OECD). That is, the state of learners in terms of literacy is still low, especially science. The average value of metacognitive skills of students in each school ranged from 64-75, including the high criteria. Learners are well aware of her capabilities and control the learning process from planning to evaluate themselves after solving the problem. Based on the calculation of product moment correlation, the relationship between scientific literacy and metacognitive learners are very weak with a value of r = 0.006. The students are not familiar with the question of scientific literacy, so that the value of scientific literacy is low in metacognitive learners high.